Avaliação do jogo “Ciclo do Poder” para promoção da dignidade menstrual em espaços de educação não formal - Valle, Tânia Zaverucha do; Santos, Açucena Melo Araújo dos; Dias, Cynthia Macedo; Carvalho, Flavia Garcia de; Spiegel, Carolina Nascimento; Maia, Renata Monteiro; Bruno, Rafaela Vieira (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2025)
Introduction: The cooperative board game “Ciclo do Poder” aims to facilitate the dialogue about menstruation and to promote attitudes in favor of menstrual dignity. Objective: To present the results of observations from game sessions conducted in non-formal educational spaces in order to assess the game’s contributions in disseminating information about the menstrual cycle. Additionally, it examines player performance, the importance of mixed groups, cards that raised doubts, and game duration. Methodology: Mediated game sessions and application of observational sheets, filled out by the team. Results: The observations helped to verify the values incorporated in the game, the importance of mediation, the benefits of mixed groups, necessary design and wording adjustments for the cards, and game balancing.